Tèngka tradition in Madura: Constructive role of ulama as religious and cultural leaders - Jannah, Hasanatul; Purwanto, Danang (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This research explores the tradition of tèngka in Madura society, and how scholars can appear as controllers in tardisitèngka. The tradition of tèngka in Madura society is the grammar and rules that form the mindset, behavior and customs of Madura. Tèngka covers all aspects of Madura people's lives to manifest in the pattern of daily life relations and manifests in rituals that have become habits in the midst of Madura society, ranging from various religious rituals, marriage rituals, birth rituals, to death rituals. Tèngka as a culture in place as customary law, then the practice of tèngka in Madura society is difficult to avoid even refute. Because it has been practiced and preserved for generations, and becomes an increasingly powerful and deep-rooted tradition. One of the important roles of Madura scholars besides being a religious leader, as well as the controller of the tèngka tradition. The significance in the tradition of tèngka placing Madura scholars as the most decisive figure in the formation of Madura society. Madura scholars not only became religious figures, but also became cultural figures who accumulated as guardians, movers, maintainers and at the same time controllers of the tèngka tradition.